Some Facts on Problematic Internet Use and Sleep Disturbance among Adolescents - Sarah ISLAMIE FARSANI; Khadija ALLAHBAKHSHI; Ali Asghar VALIPOUR; Abdollah MOHAMMADIAN-HAFSHEJANI (Tehran University of Medical Sciences, 2016)
Some Facts on Problematic Internet Use and Sleep Disturbance among Adolescents